IMPLEMENTASI MANAJEMEN TALENTA ASN UNTUK MENINGKATKAN LAYANAN PUBLIK DI DPMPTSP TAKALAR - Nasir, Nasir (STISIP Widyapuri Mandiri, 2025)
This study aims to analyze the implementation of talent management of the State Civil Apparatus (ASN) in improving the quality of public services at the Takalar Regency Investment and One-Stop Integrated Services Office (DPMPTSP). The main problem in this study is the lack of optimal management of ASN talent which affects the effectiveness of public services. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The subjects of the study include structural officials and ASN staff involved in the process of service and human resource management. The results of the study show that the implementation of talent management at DPMPTSP Takalar is still limited and has not been systematically structured. The mapping of ASN potential has not been carried out formally, career development has not been directed through planned programs, and training is still general. However, there are positive initiatives from ASN leaders and individuals that show the potential for the development of the talent system in the future. These findings show that there is a gap between ideal expectations and practice in the field. The contribution of this study is to provide an empirical overview of the conditions of implementation of ASN talent management in local government agencies, as well as to be the basis for formulating competency-based and merit-based HR management policies. This research also contributes to the development of human resource management science in the public sector, especially in the context of improving professionalism and quality of public services through talent management strategies.